Policy coordination in a monetary union - Carlberg, Michael (Berlin ; New York : Springer, 2003)
This comprehensive study of the international coordination of economic policy in a monetary union, discusses the process of policy competition and the structure of policy cooperation.
Includes bibliographical references (p. [259]-269) and index.
oif 31/08/15
Loan
Keywords: Monetary policy; Monetary unions; European Union countries -- Economic policy